Development of a Web-Based Tourist Bus Rental Application at PO Tali Jaya - Firmansyah, Aldy; Siswanto, Teddy; Santoso, Gatot Budi (Penerbitan Universitas Trisakti, 2025)
Advancements in information and communication technology have revolutionized the transportation sector, including bus services provided by PO Tali Jaya in Cilegon, Banten. The main challenge faced is efficiently managing bus rentals, organizing customer data, managing rental reports, and improving service levels. This study proposes the use of a web-based bus rental application to enhance efficiency and service. Through interviews with customers and management, this system is designed to streamline the bus booking process and provide better operational access. The research references transportation management theory and web system development to meet industry standards. By utilizing the waterfall methodology with stages such as requirement system, analysis, design, coding, testing, and maintenance, a comprehensive and organized system is created. The final result is a web-based bus rental application with comprehensive features such as a calendar schedule for each bus, digitalized rental data archiving, and well-structured rental financial reports. It is expected that implementing this system will improve operational efficiency, simplify rental transaction data management, provide better services, and serve as a model for other transportation companies.